WYDZIAŁ PRAWA W LATACH 1919 - 1990 - Olszewski, Henryk (Wydział Prawa i Administracji UAM, 1999)
The Faculty of Law and Administration of the Adam Mickiewicz University in Poznań has come into existence on May 7,1919, together with the University as a whole. The Author describes organizational beginnings involved with creating the Faculty and cites the names of many eminent professors engaged in the cause as well as primary localization of its particular organizational units and, also, methods of recruitment and teaching students within the period before the World War II. After a presentation of main researches done under the auspices of the Faculty, the Author recalls first honoris causa doctorates and initiation of co-operation with foreign academic centres in France, Belgium, Italy and Spain - what was a sign of increasing prestige of the Faculty. Next the Author draws up vicissitudes o f the Faculty and its employees in the period of World War II as well as first, very difficult years of the reconstruction of scientific and didactic basis after the nazi occupation (first academic year was shortened and lasted from April 15 to September 31, 1945). Succesive years of communist indoctrination and „politization” of universities have left their heavy imprint on the Faculty; courses and conversatories found „needless” have been abolished, professors found „superfluous” were pensioned regardless their age. This short historical survey, with particular reference to such dates as 1956, 1958 and 1968, is ended by the Author with a presentation of the Faculty situation on the turn o f the eighties and the nineties and, on this general background, the position of the Faculty within new social and economic factual circumstances is also discussed.
THE FACULTY OF LAW WITHIN THE PERIOD 1919-1990